Babesia microti Aldo-keto Reductase-Like Protein Involved in Antioxidant and Anti-parasite Response - Huang, Qiang; Cao, Jie; Zhou, Yongzhi; Huang, Jingwei; Gong, Haiyan; Zhang, Houshuang; Zhu, Xing-Quan; Zhou, Jinlin (Frontiers in Microbiology, 2017)
The intraerythrocytic apicomplexan Babesia microti is the primary causative agent of human babesiosis, which is an infectious disease that occurs in various regions around the world. Although the aldo-keto reductases (AKRs) of this parasite have been sequenced and annotated, their biological properties remain unknown. AKRs are a superfamily of enzymes with diverse functions in the reduction of aldehydes and ketones. In the present study, we cloned the full-length cDNA of a B. microti aldo-keto reductase-like protein (BmAKR) and analyzed the deduced amino acid sequence of the BmAKR protein. This protein has a conserved AKR domain with an N-terminal signal sequence. Bmakr was upregulated on the 8th day after infection, whereas it was downregulated during the later stages. The recombinant protein of BmAKR was expressed in a glutathione S-transferase-fused soluble form in Escherichia coli. Western blot analysis showed that the mouse anti-BmAKR antibody recognized native BmAKR from a parasite lysate. Immunofluorescence microscopy localized BmAKR to the cytoplasm of B. microti merozoites in mouse RBCs. Bmakr expression was significantly upregulated in the presence of oxidant stress. Atovaquone, a known anti-babesiosis drug, and robenidine, a known anti-coccidiosis drug, induced upregulation of Bmakr mRNA, thereby suggesting that Bmakr may be involved in drug response